The Ex-utero intrapartum treatment procedure: a narrative review - Gaffuri, Michele; Raffaeli, Genny; Bullejos Garcia, Elena Emilia; Perugino, Giuseppe; Cassardo, Ottavio; Persico, Nicola; Colnaghi, Mariarosa; Garrido, Felipe; Villamor, Eduardo; Cetin, Irene; Fumagalli, Monica; Pignataro, Lorenzo; et al. (Frontiers in Pediatrics, 2025)
The “Ex Utero Intrapartum Treatment” (EXIT) procedure is a specialized surgical technique used during cesarean delivery to perform life-saving fetal interventions while maintaining placental circulation. By preserving feto-placental gas exchange, EXIT enables the treatment of severe conditions such as predictable severe breathing difficulties at birth. EXIT's origins date back to removing tracheal occlusion devices used for congenital diaphragmatic hernias. It has since expanded to treat conditions such as congenital high airway obstruction syndrome and airway compression by masses. Despite the risks of adverse maternal and fetal events, it shows high perinatal survival rates. The success of EXIT depends on an accurate prenatal diagnosis through fetal ultrasound and magnetic resonance imaging. Anesthetic management differs from standard cesarean sections, balancing the need for uterine relaxation and avoiding maternal-fetal risks. Inhaled anesthetics are preferred, although recent studies suggest the potential of neuraxial anesthesia combined with tocolytics. Although the EXIT procedure can be performed safely in specialized centers, it does carry risks for both the mother and the fetus. Neonatal mortality and complications vary depending on indications and postnatal management. Research and clinical practice must advance to improve safety and efficacy.